A study of perceived employability among undergraduate in Universiti Teknologi MARA (UiTM) Cawangan Melaka Kampus Bandaraya / Mohd Hafizzudin Shahrifudin - Shahrifudin, Mohd Hafizzudin (Faculty of Business and Management, 2018)
Malaysia, the rate of unemployment among fresh graduates is high since many graduates are found lacking of what are needed to acquire and maintain their jobs. An employability skill is a passport for an individual to step into a challenging working industry. The more employability skills that they possess, the greater the possibility and chance for them to get better placement.